A kind of corrosion-resistant rubber and preparation method thereof

By using fluorosilicone rubber, modified nitrile rubber and ethylene propylene ternary rubber, and specific modification of nitrile rubber to form a crosslinking network structure, the problem of degradation of ordinary rubber in corrosive environments is solved, and the problem of degradation of performance of ordinary rubber in corrosive environments is achieved. Rubber materials with high corrosion resistance and high mechanical strength.

CN118755275BActive Publication Date: 2025-02-07FOSHAN MANQIANG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411065586.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-02-07
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The performance of ordinary rubber materials in corrosive environments such as acid and alkali have rapidly declined, and their service life has been greatly shortened, increasing maintenance costs and safety risks.

Method used

Fluorosilicone rubber, modified nitrile rubber and ethylene propylene ternary rubber are used as rubber matrix, and perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyllithium, cyclopentane and stearic acid Zinc modifys nitrile rubber to form a crosslinking network structure to improve the corrosion resistance and mechanical strength of the rubber.

Benefits of technology

It significantly improves the corrosion resistance and mechanical strength of rubber, extends service life, and reduces maintenance costs and safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant rubber and a preparation method thereof, which relates to the field of rubber, and comprises the following raw materials by weight: 20-60 parts of fluorosilicone rubber; 30-60 parts of modified nitrile rubber; 10-40 parts of EPDM rubber; 10-20 parts of filler; 2-8 parts of accelerator; 5-10 parts of silane coupling agent; 1-5 parts of sulfur; the modified nitrile rubber comprises the following raw materials modified and prepared: nitrile rubber, perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate. The present application has the effect of improving the corrosion resistance of rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber, in particular to a corrosion-resistant rubber and a preparation method thereof. Background Art

[0002] Currently, rubber products are widely used in industrial production and daily life, but the performance of ordinary rubber materials declines rapidly in corrosive environments such as acids and alkalis, and their service life is greatly shortened, which increases maintenance costs and safety risks. Therefore, the development of corrosion-resistant rubber materials has become an urgent need in the industry. Summary of the invention

[0003] In order to improve the corrosion resistance of rubber, the present application provides a corrosion-resistant rubber and a preparation method thereof.

[0004] In the first aspect, the present application provides a corrosion-resistant rubber adopting the following technical solution:

[0005] A corrosion-resistant rubber comprises the following raw materials in parts by weight: 20-60 parts of fluorosilicone rubber; 30-60 parts of modified nitrile rubber; 10-40 parts of EPDM rubber; 10-20 parts of filler; 2-8 parts of accelerator; 5-10 parts of silane coupling agent; and 1-5 parts of sulfur. The modified nitrile rubber is prepared by modifying the following raw materials: nitrile rubber, perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate.

[0006] By adopting the above technical scheme: This application uses fluorosilicone rubber, modified nitrile rubber and EPDM rubber as the rubber matrix. The EPDM rubber and modified nitrile rubber have good mutual solubility, and then cooperate with fluorosilicone rubber to further improve the corrosion resistance of the rubber. The filler can be evenly dispersed in the rubber and combined with the rubber to form a dense and stable cross-linked structure, thereby effectively improving the corrosion resistance and mechanical strength of the rubber.

[0007] Preferably, the preparation method of the modified nitrile rubber is: after mixing and stirring 10-30 parts by weight of perfluoropolyether methyl ester, 10-20 parts by weight of butadiene-styrene copolymer, 1-5 parts by weight of n-butyl lithium and 2-8 parts by weight of cyclopentane, kneading with 20-40 parts by weight of nitrile rubber and 5-15 parts by weight of zinc stearate to obtain the modified nitrile rubber.

[0008] By adopting the above technical scheme: using perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate to modify nitrile rubber, perfluoropolyether methyl ester has good chemical resistance and can improve the corrosion resistance of nitrile rubber, butadiene-styrene copolymer and perfluoropolyether methyl ester are reacted by n-butyl lithium and cyclopentane, so that perfluoropolyether methyl ester is grafted on the nitrile rubber to form a cross-linked network structure, and zinc stearate is used as an active agent to increase the cross-linking density of the nitrile rubber, thereby further improving the tensile strength and stability of the rubber.

[0009] Preferably, the weight ratio of the perfluoropolyether methyl ester, butadiene-styrene copolymer and nitrile rubber is (0.8-0.9):(0.4-0.6):1.

[0010] By adopting the above technical scheme: when perfluoropolyether methyl ester, butadiene-styrene copolymer and nitrile rubber are in a specific weight ratio, the three work together to further improve the mechanical strength of the rubber, and perfluoropolyether methyl ester is grafted on the nitrile rubber to form a cross-linked network structure, which reduces the interaction between the molecular chains of the nitrile rubber and effectively provides the dispersion of the filler in the rubber matrix, thereby further improving the tensile strength and corrosion resistance of the rubber.

[0011] Preferably, the EPDM rubber is a modified EPDM rubber, and the preparation method of the modified EPDM rubber is: 5-15 parts by weight of stearic acid and 20-40 parts by weight of thionyl chloride are mixed and stirred, and after drying, 2-8 parts by weight of tea polyphenols, 40-60 parts by weight of ethyl acetate and 1-2 parts by weight of pyridine are added to heat and react, washed and dried, and then mixed with 10-30 parts by weight of EPDM rubber to obtain the modified EPDM rubber.

[0012] By adopting the above technical scheme: tea polyphenols have hydrophilic and oleophobic properties, which easily lead to a decrease in the tensile strength of EPDM rubber. After the reaction of stearic acid and tea polyphenols, the tensile strength of EPDM rubber can be effectively improved. Sulfoxide chloride activates the hydroxyl groups in tea polyphenols, promotes the modification of EPDM rubber, and thus improves the chemical resistance of EPDM rubber.

[0013] Preferably, the Mooney viscosity of the EPDM rubber is 56-66MU, and the ethylene content is 50-60wt%.

[0014] By adopting the above technical scheme: selecting EPDM rubber with appropriate Mooney viscosity can make EPDM rubber easier to mix evenly with other rubbers, while making the rubber have good mechanical properties; and selecting appropriate ethylene content helps to improve the tensile strength of the rubber and the extrusion characteristics of the rubber, thereby producing a rubber with good corrosion resistance.

[0015] Preferably, the weight ratio of stearic acid, thionyl chloride, tea polyphenols and EPDM rubber is (0.6-0.7): (1.7-1.9): (0.15-0.2): 1.

[0016] By adopting the above technical scheme: when stearic acid, thionyl chloride, tea polyphenols and EPDM rubber are in a specific weight ratio, tea polyphenols can increase the crosslinking density of EPDM rubber and improve the dispersibility of fillers in rubber; stearic acid and thionyl chloride modify tea polyphenols; thionyl chloride activates the phenolic hydroxyl groups of tea polyphenols, so that stearic acid and tea polyphenols react to generate esterification products, thereby increasing the fat solubility of tea polyphenols and coating them on the surface of EPDM rubber, thereby improving the corrosion resistance of EPDM rubber.

[0017] Preferably, the weight ratio of the fluorosilicone rubber, the modified nitrile rubber and the modified EPDM rubber is (0.6-0.72):1:(0.64-0.72).

[0018] By adopting the above technical solution: when fluorosilicone rubber, modified nitrile rubber and modified EPDM rubber are in a specific weight ratio, the three work together to produce a synergistic effect, give full play to their respective excellent characteristics, and effectively improve the corrosion resistance and tensile strength of the rubber.

[0019] Preferably, the filler includes one of carbon black, silicon dioxide and zinc oxide.

[0020] Preferably, the accelerator includes one of accelerator TMTD and accelerator TBBS.

[0021] By adopting the above technical solution: selecting suitable fillers and accelerators can effectively improve the corrosion resistance of rubber.

[0022] In the second aspect, the present application provides a method for preparing corrosion-resistant rubber using the following technical solution:

[0023] A method for preparing corrosion-resistant rubber comprises the following steps: mixing and heating fluorosilicone rubber, modified nitrile rubber and EPDM rubber, then sequentially adding filler, accelerator and silane coupling agent for kneading, then adding sulfur for kneading and discharging to obtain the corrosion-resistant rubber.

[0024] By adopting the above technical solution, the components are simply mixed in a step sequence to produce a rubber with high corrosion resistance.

[0025] In summary, this application has the following beneficial technical effects:

[0026] 1. This application uses fluorosilicone rubber, modified nitrile rubber and EPDM rubber as the rubber matrix. The EPDM rubber and modified nitrile rubber have good mutual solubility, and then cooperate with fluorosilicone rubber to further improve the corrosion resistance of the rubber. The filler can be evenly dispersed in the rubber and combined with the rubber to form a dense and stable cross-linked structure, thereby effectively improving the corrosion resistance and mechanical strength of the rubber.

[0027] 2. Perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate are used to modify nitrile rubber. Perfluoropolyether methyl ester has good chemical resistance and can improve the corrosion resistance of nitrile rubber. n-butyl lithium and cyclopentane initiate the reaction of butadiene-styrene copolymer and perfluoropolyether methyl ester, so that perfluoropolyether methyl ester is grafted on nitrile rubber to form a cross-linked network structure. Zinc stearate is used as an active agent to increase the cross-linking density of nitrile rubber, thereby further improving the tensile strength and stability of the rubber. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to examples and comparative examples.

[0029] Example

[0030] Example 1

[0031] A method for preparing corrosion-resistant rubber:

[0032] 20g of fluorosilicone rubber, 30g of modified nitrile rubber and 10g of EPDM rubber were put into an internal mixer, heated to 80°C at a speed of 50rpm and mixed for 10min, then 10g of filler, 2g of accelerator and 5g of silane coupling agent were added in sequence, the temperature was raised to 120°C and mixing was continued for 10min, then 1g of sulfur was added and the temperature was maintained at 120°C and mixing was continued for 10min before discharging to obtain corrosion-resistant rubber.

[0033] The EPDM rubber is Korean SK model S5527F, with a Mooney viscosity of 57MU and an ethylene content of 54%; the fluorosilicone rubber is brand ELASTOSILR 901 / 60, produced by Wacker Chemical (China) Co., Ltd.; the filler is zinc oxide; the accelerator is accelerator TMTD; and the silane coupling agent is KH550.

[0034] The preparation method of the modified nitrile rubber is as follows: 10g of perfluoropolyether methyl ester, 10g of butadiene-styrene copolymer, 1g of n-butyl lithium and 2g of cyclopentane are put into a stirrer and mixed and stirred at room temperature for 30 minutes, and then 20g of nitrile rubber and 5g of zinc stearate are added into a mixer and mixed for 20 minutes to obtain the modified nitrile rubber. The nitrile rubber is JSR, model N230S; the perfluoropolyether methyl ester is Mai De Hao, model MDH; and the butadiene-styrene copolymer is Sabic, brand C6200-111.

[0035] Example 2

[0036] A method for preparing corrosion-resistant rubber:

[0037] 60g of fluorosilicone rubber, 60g of modified nitrile rubber and 40g of EPDM rubber were put into an internal mixer, heated to 80°C at a speed of 50rpm and mixed for 10min, then 20g of filler, 8g of accelerator and 10g of silane coupling agent were added in sequence, the temperature was raised to 120°C and mixed for 10min, then 5g of sulfur was added and mixed at 120°C for 10min before discharging to obtain corrosion-resistant rubber.

[0038] The EPDM rubber used is the model J-3092E of Jilin Petrochemical; the fluorosilicone rubber used is the brand ELASTOSILR901 / 60, produced by Wacker Chemical (China) Co., Ltd.; the filler is silicon dioxide; the accelerator is accelerator TBBS; and the silane coupling agent is KH550.

[0039] The preparation method of the modified nitrile rubber is as follows: 10g of perfluoropolyether methyl ester, 10g of butadiene-styrene copolymer, 1g of n-butyl lithium and 2g of cyclopentane are put into a stirrer and mixed and stirred at room temperature for 30 minutes, and then 20g of nitrile rubber and 5g of zinc stearate are added into a mixer and mixed for 20 minutes to obtain the modified nitrile rubber. The nitrile rubber is JSR, model N230S; the perfluoropolyether methyl ester is Mai De Hao, model MDH; and the butadiene-styrene copolymer is Sabic, brand C6200-111.

[0040] Example 3

[0041] A method for preparing corrosion-resistant rubber:

[0042] 40g of fluorosilicone rubber, 45g of modified nitrile rubber and 25g of EPDM rubber were put into an internal mixer, heated to 80°C at a speed of 50rpm and mixed for 10min, then 15g of filler, 5g of accelerator and 7.5g of silane coupling agent were added in sequence, the temperature was raised to 120°C and mixing was continued for 10min, then 3g of sulfur was added and the temperature was maintained at 120°C and mixing was continued for 10min before discharging to obtain corrosion-resistant rubber.

[0043] The EPDM rubber is Korean SK model S5527F, with a Mooney viscosity of 57MU and an ethylene content of 54%; the fluorosilicone rubber is brand ELASTOSILR 901 / 60, produced by Wacker Chemical (China) Co., Ltd.; the filler is carbon black; the accelerator is accelerator TMTD; and the silane coupling agent is KH550.

[0044] The preparation method of the modified nitrile rubber is as follows: 10g of perfluoropolyether methyl ester, 10g of butadiene-styrene copolymer, 1g of n-butyl lithium and 2g of cyclopentane are put into a stirrer and mixed and stirred at room temperature for 30 minutes, and then 20g of nitrile rubber and 5g of zinc stearate are added into a mixer and mixed for 20 minutes to obtain the modified nitrile rubber. The nitrile rubber is JSR, model N230S; the perfluoropolyether methyl ester is Mai De Hao, model MDH; and the butadiene-styrene copolymer is Sabic, brand C6200-111.

[0045] Example 4

[0046] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that: the method for preparing modified nitrile rubber is as follows: 10g of perfluoropolyether methyl ester, 30g of butadiene-styrene copolymer, 5g of n-butyl lithium, and 8g of cyclopentane are put into a stirrer and mixed and stirred at room temperature for 30 minutes, and then added with 40g of nitrile rubber and 15g of zinc stearate into a mixer and mixed for 20 minutes to obtain modified nitrile rubber.

[0047] Example 5

[0048] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that: in the process of preparing modified nitrile rubber, the input amount of perfluoropolyether methyl ester is 24g, the input amount of butadiene-styrene copolymer is 12g, and the input amount of nitrile rubber is 30g.

[0049] Example 6

[0050] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that: in the process of preparing modified nitrile rubber, the input amount of perfluoropolyether methyl ester is 27g, the input amount of butadiene-styrene copolymer is 18g, and the input amount of nitrile rubber is 30g.

[0051] Example 7

[0052] A method for preparing corrosion-resistant rubber, which is different from Example 6 in that an equal amount of EPDM rubber is replaced with modified EPDM rubber, wherein the preparation method of the modified EPDM rubber is as follows: 5g of stearic acid and 20g of thionyl chloride are mixed and stirred at a temperature of 60°C for 4h, transferred to an oven and dried at a temperature of 100°C for 2h, then 2g of tea polyphenols, 40g of ethyl acetate and 1g of pyridine are added, heated to 70°C for reaction for 8h, washed and dried for 4h, and then mixed with 10g of EPDM rubber to obtain the modified EPDM rubber.

[0053] Example 8

[0054] A method for preparing corrosion-resistant rubber, which is different from Example 6 in that an equal amount of EPDM rubber is replaced with modified EPDM rubber, wherein the preparation method of the modified EPDM rubber is as follows: 15g of stearic acid and 40g of thionyl chloride are mixed and stirred at a temperature of 60°C for 4h, transferred to an oven and dried at a temperature of 100°C for 2h, then 8g of tea polyphenols, 60g of ethyl acetate and 2g of pyridine are added, heated to 70°C for reaction for 8h, washed and dried for 4h, and then mixed with 30g of EPDM rubber to obtain the modified EPDM rubber.

[0055] Example 9

[0056] A method for preparing corrosion-resistant rubber, which is different from Example 8 in that: the input amount of stearic acid is 12g, the input amount of thionyl chloride is 34g, the input amount of tea polyphenols is 3g, and the input amount of EPDM rubber is 20g.

[0057] Example 10

[0058] A method for preparing corrosion-resistant rubber, which is different from Example 8 in that: the input amount of stearic acid is 14g, the input amount of thionyl chloride is 38g, the input amount of tea polyphenols is 4g, and the input amount of EPDM rubber is 20g.

[0059] Embodiment 11

[0060] A method for preparing corrosion-resistant rubber, which is different from Example 10 in that the input amount of fluorosilicone rubber is 30g, the input amount of modified nitrile rubber is 50g, and the input amount of modified EPDM rubber is 32g.

[0061] Example 12

[0062] A method for preparing corrosion-resistant rubber, which is different from Example 10 in that the input amount of fluorosilicone rubber is 36g, the input amount of modified nitrile rubber is 50g, and the input amount of modified EPDM rubber is 36g.

[0063] Comparative Example

[0064] Comparative Example 1

[0065] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that an equal amount of modified nitrile rubber is replaced by nitrile rubber.

[0066] Comparative Example 2

[0067] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that an equal amount of EPDM rubber is replaced by fluorosilicone rubber.

[0068] Comparative Example 3

[0069] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that an equal amount of modified nitrile rubber is replaced by fluorosilicone rubber.

[0070] Comparative Example 4

[0071] A method for preparing corrosion-resistant rubber, which is different from Example 3 in that an equal amount of modified nitrile rubber is replaced by styrene-butadiene rubber.

[0072] Performance testing:

[0073] Tensile strength: The rubbers prepared in Examples 1-12 and Comparative Examples 1-4 were tested with reference to the national standard GB / T528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”.

[0074] Corrosion resistance: The rubbers prepared in Examples 1-12 and Comparative Examples 1-4 were placed in 10% by mass dilute hydrochloric acid and 10% by mass dilute sodium hydroxide solution, respectively, and then immersed for 24 hours and subjected to a tensile strength test;

[0075]

[0076]

[0077] According to the data comparison of Examples 1-4 and Comparative Examples 1-4, the present application uses fluorosilicone rubber, modified nitrile rubber and EPDM rubber as rubber matrices. The EPDM rubber and modified nitrile rubber have good mutual solubility, and then cooperate with the fluorosilicone rubber to further improve the corrosion resistance of the rubber. The filler can be evenly dispersed in the rubber and combined with the rubber to form a dense and stable cross-linked structure, thereby effectively improving the corrosion resistance and mechanical strength of the rubber; perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate are used to modify the nitrile rubber. Perfluoropolyether methyl ester has good chemical resistance and can improve the corrosion resistance of the nitrile rubber. The reaction of butadiene-styrene copolymer and perfluoropolyether methyl ester is initiated by n-butyl lithium and cyclopentane, so that the perfluoropolyether methyl ester is grafted on the nitrile rubber to form a cross-linked network structure. Zinc stearate is used as an activator to increase the cross-linking density of the nitrile rubber, thereby further improving the tensile strength and stability of the rubber.

[0078] According to the data comparison of Examples 3-6, it can be obtained that when perfluoropolyether methyl ester, butadiene-styrene copolymer and nitrile rubber are in a specific weight ratio, the three work together to further improve the mechanical strength of the rubber. Perfluoropolyether methyl ester is grafted on the nitrile rubber to form a cross-linked network structure, which reduces the interaction between the nitrile rubber molecular chains and effectively provides the dispersion of the filler in the rubber matrix, thereby further improving the tensile strength and corrosion resistance of the rubber.

[0079] According to the data comparison of Examples 6-8, tea polyphenols have hydrophilic and oleophobic properties, which can easily lead to a decrease in the tensile strength of EPDM rubber. However, after the reaction of stearic acid and tea polyphenols, the tensile strength of EPDM rubber can be effectively improved. Sulfoxide chloride activates the hydroxyl groups in tea polyphenols, promotes the modification of EPDM rubber, and thus improves the chemical resistance of EPDM rubber.

[0080] According to the data comparison of Examples 8-10, it can be obtained that when stearic acid, thionyl chloride, tea polyphenols and EPDM rubber are in a specific weight ratio, tea polyphenols can increase the crosslinking density of EPDM rubber and improve the dispersibility of fillers in the rubber. Stearic acid and thionyl chloride modify tea polyphenols. Thionyl chloride activates the phenolic hydroxyl groups of tea polyphenols, so that stearic acid and tea polyphenols react to form an esterification product, thereby increasing the fat solubility of tea polyphenols and coating them on the surface of EPDM rubber, thereby improving the corrosion resistance of EPDM rubber.

[0081] According to the data comparison of Examples 10-12, when fluorosilicone rubber, modified nitrile rubber and modified EPDM rubber are in a specific weight ratio, the three work together to produce a synergistic effect, give full play to their respective excellent characteristics, and effectively improve the corrosion resistance and tensile strength of the rubber.

[0082] The specific embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A corrosion-resistant rubber, characterized in that: The invention comprises the following raw materials in parts by weight: 20-60 parts of fluorosilicone rubber; 30-60 parts of modified nitrile rubber; 10-40 parts of EPDM rubber; 10-20 parts of filler; 2-8 parts of accelerator; 5-10 parts of silane coupling agent; 1-5 parts of sulfur; the modified nitrile rubber is prepared by modifying the following raw materials: nitrile rubber, perfluoropolyether methyl ester, butadiene-styrene copolymer, n-butyl lithium, cyclopentane and zinc stearate; the preparation method of the modified nitrile rubber is as follows: 10-30 parts by weight of perfluoropolyether methyl ester, 10-20 parts by weight of butadiene-styrene copolymer and 1-5 parts by weight of n-butyl lithium and 2-8 parts by weight of cyclopentane are mixed and stirred, and then mixed with 20-40 parts by weight of nitrile rubber and 5-15 parts by weight of zinc stearate to obtain the modified nitrile rubber.

2. The corrosion-resistant rubber according to claim 1, characterized in that: The weight ratio of the perfluoropolyether methyl ester, butadiene-styrene copolymer and nitrile rubber is (0.8-0.9): (0.4-0.6):

1.

3. The corrosion-resistant rubber according to claim 1, characterized in that: The EPDM rubber is a modified EPDM rubber. The preparation method of the modified EPDM rubber is as follows: 5-15 parts by weight of stearic acid and 20-40 parts by weight of thionyl chloride are mixed and stirred, 2-8 parts by weight of tea polyphenols, 40-60 parts by weight of ethyl acetate and 1-2 parts by weight of pyridine are added after drying and heated for reaction, the mixture is washed and dried, and then mixed with 10-30 parts by weight of EPDM rubber to obtain the modified EPDM rubber.

4. The corrosion-resistant rubber according to claim 1, characterized in that: The Mooney viscosity of the EPDM rubber is 56-66MU, and the ethylene content is 50-60wt%.

5. The corrosion-resistant rubber according to claim 3, characterized in that: The weight ratio of stearic acid, thionyl chloride, tea polyphenols and EPDM rubber is (0.6-0.7): (1.7-1.9): (0.15-0.2):

1.

6. The corrosion-resistant rubber according to claim 3, characterized in that: The weight ratio of the fluorosilicone rubber, the modified nitrile rubber and the modified EPDM rubber is (0.6-0.72):1:(0.64-0.72).

7. The corrosion-resistant rubber according to claim 1, characterized in that: The filler includes one of carbon black, silicon dioxide and zinc oxide.

8. The corrosion-resistant rubber according to claim 1, characterized in that: The accelerator includes one of accelerator TMTD and accelerator TBBS.

9. A method for preparing corrosion-resistant rubber, characterized in that: The method for preparing the corrosion-resistant rubber according to any one of claims 1 to 8 comprises the following steps: mixing and heating fluorosilicone rubber, modified nitrile rubber and EPDM rubber, adding filler, accelerator and silane coupling agent in sequence and kneading, adding sulfur and kneading, and then discharging to obtain the corrosion-resistant rubber.

Citation Information

Patent Citations

  • Rubber sealing composite material and preparation method thereof

    CN108610525A

  • Engine fuel rubber pipe and preparation method thereof

    CN109265883A